Structural and Stratigraphic Interpretations for Mishrif Formation in Kumait Oil Field, Using Seismic Reflection Data, Southern-Eastern Iraq - Khalel, Rusul A.; Al-Rahim, Ali M. (Iraqi Journal of Science, 2024)
The Kumait oil field is located in the Maysan Governorate southeastern Iraq, which was studied and interpreted by using 2D and 3D seismic data provided by the Oil Exploration Company using Petrel software. The study concerned the Mishrif Formation belongs to the Cretaceous Age. The reflector was detected based on synthetic seismograms and well logs for Kt-1 well. Structural maps (two-way time, velocity, and depth) were derived from seismic reflection interpretations to show several structural features, such as four isolated irregular enclosures representing the Kumait structure plunging NW-SE and demonstrating that the Kumait oil field is influenced by the Najd fault system trending NW-SE. The stratigraphic interpretation used the variance attribute to delineate the edge of the fault, which extended from the Mishrif Formation with a depth of 3090m and used the Direct Hydrocarbon Indicators (DHI) to identify the stratigraphic features in the research region and the extraction of seismic attributes. The applied seismic attributes, such as the instantaneous phase, show dim spots, flat spots, and mounds and is followed by down-lap; the instantaneous frequency, which offers low-frequency areas indicating a high probability of hydrocarbon accumulation; and the RMS amplitude, which shows high amplitude in the seismic data that conforms to the structure and confirms the presence of hydrocarbon.